Efektivitas Pemberian Insulin Bolus Pada Pasien Ketoasidosis Diabetikum: Literature Review - Husni, Lailatul; Hidayah, Nurul (Universitas Muhammadiyah Magelang, 2025)
Diabetic Ketoacidosis is a complication of Diabetes Mellitus characterized by high levels of ketones in the body. This ketoacidosis occurs due to the absence of insulin produced by the pancreas. This condition occurs due to insulin deficiency, namely the breakdown of fat into free fatty acids and glycerol. Diabetic Ketoacidosis is an acute complication of Diabetes Mellitus that must be treated quickly and appropriately considering the very high mortality rate. Management of Diabetic Ketoacidosis patients is carried out by administering bolus insulin. Bolus insulin is an intensive insulin therapy that involves taking a combination of insulin. In this bolus insulin has a strong but short-lived effect on blood sugar and can be an ideal supplement for people with Diabetic Ketoacidosis. The purpose of this study was to determine the effectiveness of administering bolus insulin to patients with Diabetic Ketoacidosis. The methods used in this study were three databases, namely Google Scholar, PubMed, and Science Direct. Data collection techniques by searching for reputable and high-quality journal articles using boolean operators (AND, OR, NOT, or AND NOT). The keywords in this literature review are adjusted to the Medical Subject Heading (MeSH). The final results carried out based on the eligibility of the inclusion and exclusion criteria obtained as many as 8 articles that could be used in this literature review research. The conclusion is that giving bolus insulin to patients with Diabetic Ketoacidosis is not effective. Many experts say that giving rapid bolus insulin to patients with Diabetic Ketoacidosis can cause dangers including hypoglycemia, hypokalemia, and cerebral edema if glucose levels are corrected too quickly.